Dynamics of Dry Matter, Organic Matter and Crude Protein in the Leaves of Four Varieties of Brachiaria Brizantha at the Vegetative Stage, Under the Ecological Conditions of Kisangani in the DRC - Ngakpa, Maurice D.; Musalizi, Roger-Lafleur M.; Mukandama, Jean-Pierre N.; Saile, Joseph I.; Masengo, Colette A.; Nyiwa, Ngbolua Koto-te- (Budapest International Research and Critics University, 2024)
The present work aimed to evaluate the variation of dry matter, organic matter and crude protein in the vegetative phase of four varieties of Brachiaria brizantha (Xaraes, Piata, Marandu and Locale) in forage cultivation. After field experimentation in a complete random block system, and laboratory analyses, the results obtained show that the dry matter content increases from the beginning tillering stage to the end tillering stage and varies according to variety. The highest dry matter content is recorded in the local variety at the late tillering stage. The crude protein content also varies depending on variety and phenological stage, the protein contents are higher at the full tillering stage in the varieties Xaraes (17.34%), Locale (15.8%) and Marandu (14.2%), while the Piata variety reaches its highest protein content from the early tillering stage (13.8%). Overall, the Xaraes variety is more protein-rich, its average protein content in the vegetative phase is 15.3%. Thus, the Xaraes variety is economically more interesting than the others, protein being the most expensive component in livestock feed. This is why this variety would be indicated to be popularized with a view to large-scale exploitation in the Kisangani region. However, additional bromatological analyzes are necessary before any decision.